PENINGKATAN HASIL BELAJAR SISWA DENGAN STRATEGI PEMBELAJARAN ACTIVE DEBATE MATA PELAJARAN PKN KELAS V SD 163098 KOTA TEBING TINGGI - Simbolon, Parida (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2016)
This purposes of this research is to improve learning result on PKn subjectÂ  through active sebate strategy. This classroom action research conducted by 2 cycles of the four phases: planning, implementation, observation, reflection. The subjects were students from class V, SD N 163098 Tebing Tinggi which amounted to 34 students. This study used a qualitative descriptive analysis technique. The results showed that the use of the inquiry method of PKn subjects can improve student learning result characterized by increased mastery learning students, namely cycle I (79.41%), cycle II (88.23 %) and complete learn the clasical equal to 88.23 %. Key Word : Learning result, Active debate straategy.